Bilateral Complete Duplication of the Ureters: A Case Report - and Aarathi Venunadan, Bindhu.S (Recent Research in Science and Technology, 2011)
Double ureter refers to presence of two separate ipsilateral ureters .It presentsÃ‚Â Ã‚Â Ã‚Â Ã‚Â complete or incomplete uretric duplication. In the complete uretric duplication the two ureters enter separately in the urinary bladder. In the incomplete duplication one ureter enters the urinary bladder after the two ureters are combined. In our routine dissection at Yenepoya medical college we found bilateral double ureter which is rare.